Exploring the limits to sustainable pellet production for international markets: The impact of increasing pellet production in the US Southeast on feedstock use, production cost and carbon sequestration in forest areas. Issue 8 (14th June 2022) - Visser, Lotte; Latta, Greg; Pokharel, Raju; Hoefnagels, Ric; Junginger, Martin
Abstract: With rising demand for wood pellets from the US Southeast (US SE), the environmental limits to additional biomass demand are increasingly questioned. This study analyses the impact of increased pellet production in the US SE until 2030 on feedstock allocation, carbon flux in forest areas and costs of pre‐treatment and transport of feedstock and pellets. This by linking locations of forest biomass supply and demand through supply‐side logistics, allocating feedstock based on lowest costs of pre‐treatment, transport of feedstock and pellets, for the entire wood products sector. The impact is analysed for different scenarios with varied pellet production levels, additional inclusion of logging residues and optimization either on costs or on maintaining total carbon stock in sourcing areas of new pellet mills. In a scenario of 20 Mt pellet production, the roundwood share increases from 0% in 2020 to 37% pulplogs and 11% sawlogs in 2030. Costs increase with 57% towards 2030 compared to 2020, largely because of higher costs for pulplogs and sawlogs. In a scenario without pellet production, forest carbon removal in the US SE is 3 Mt CO2 /year lower than in 2020. In the Reference scenario, additional carbon removal of 6, 21 and 38 Mt CO2 /year is observed for 10, 20 and 30 Mt pellet production, respectively. In all cases, the forests of the US SE remain a net sink until 2030. The impact of a selection criteria for new pellet mill locations based on keeping local growth/drain ratios above 1 in sourcing areas is small since this mostly results in displacement of impacts and does not affect the total feedstock availability. Additional mobilization of logging residues is a key strategy to reduce carbon impacts, resulting in a smaller additional flux of 2, 11 and 29 Mt CO2 /year for 10–30 Mt pellet production. Abstract : This study analyses the impact of increased pellet production in the US SE until 2030 on feedstock allocation, carbon flux in forest areas and costs of pre‐treatment and transport of feedstock and pellets. In all cases, the forests of the US SE remain a net sink until 2030. Additional mobilization of logging residues is a key strategy to reduce carbon impacts, resulting in a smaller additional flux of 2, 11 and 29 Mt CO2/y for 10 ‐ 30 Mt pellet production.